Puesta en valor de edificios patrimoniales - Piedra-Solís, Kevin (Instituto Tecnológico de Costa Rica, 2017)
In many occasions, when making interventions of historical or heritage buildings to keep them in occupation and not to leave them in oblivion, they propose to change the original use of the buildings, for uses that generate a new contribution to the society, whichcreates a challenge On how to raise something new considering the existing configuration of the building and the new space needs, without neglecting the value of historical buildings. This is why different ways exist in how buildings with heritage values should be intervened, and where concepts such as intervention, restoration, recycling, reuse and rehabilitation arise, including modern architecture in what exists in response to Need to take advantage of the spaces of these historic buildings. In the canton of Desamparados, there are two historic buildings located in the farm El Salitral, in the district of Las Gravilias, which correspond to times of the Colony and development of the towns of the time, despite the great value that encloses between its walls , The materials used, the people who inhabited them, and the creation of a museum more than 28 years ago, never developed in the proper way, including affecting the existing buildings and causing them to remain in disuse and oblivion. Therefore, the development of this graduation project, focuses on the development and development of a valuation of the existing heritage buildings of the Museum of the Carreta and the Campesino, by means of the generation of new buildings that are integrated and put In value to the already existing, allowing also to develop spaces of cultural and art, through an analysis of the current buildings and the architectural proposal of some cultural and museum spaces, that allow to reactivate the place.
el caso de las edificaciones El Salitral
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, 2017
Keywords: Patrimonio arquitectónico; Arquitectura